Pengembangan Antarmuka Web Analitik Log Deteksi Intrusi Jaringan Berbasis Suricata Menggunakan Dash - Berniawan, Nikita Putri; Saptono, Henry; Zaida, Efrizal (LPPM STT Terpadu Nurul Fikri, 2025)
The rapid growth of internet usage correlates with an increasing risk of network security threats. Attacks on network traffic may result in confidential data breaches and system disruptions. Suricata, a powerful Intrusion Detection System (IDS) tool, is used to generate rich detection logs. However, raw log data in JSON format remains difficult to analyze and interpret directly due to its complexity and large volume. This study proposes the development of a web-based application using the Dash framework to visualize intrusion detection results from Suricata. Dash is capable of presenting data in an interactive and informative manner through various components such as histograms, line charts, tables, and filter features. The purpose of this research is to assess Dash’s effectiveness in presenting intrusion data in a format that is accessible and easily interpreted by users. Evaluation results show that the Dash framework successfully visualized 24,526 alerts out of a total of 4,247,464 logs accurately. The application was also able to display all information components comprehensively and interactively. Thus, this application can contribute to improving both network security and operational efficiency.